The use of closed incision negative pressure therapy on the medial thigh donor site in transverse musculocutaneous gracilis flap breast reconstruction - Siegwart, Laura; Tapking, Christian; Diehm, Yannick; Haug, Valentin Felix; Bigdeli, Amir Khosrow; Kneser, Ulrich; Kotsougiani-Fischer, Dimitra (Journal of Clinical Medicine, 2022)
The objective of this study was to examine the impact of closed incision negative pressure therapy (CINPT) on donor site complications and patient perceptions in transverse musculocutaneous gracilis (TMG) flap breast reconstruction. Our institution conducted a retrospective cohort study, including all patients with TMG flap breast reconstruction from 1 January 2010 to 31 December 2021. Patients were grouped according to conventional wound management or CINPT. Outcomes were surgical site complications, fluid drainage, time to drain removal, and in-hospital stay length. A patient survey was created. A total of 56 patients with 83 TMG flaps were included (control group: 35 patients with 53 TMG flaps; CINPT group: 21 patients with 30 TMG flaps). Patient characteristics were similar in both groups. The flap width was significantly larger in the CINPT group (8.0 cm vs. 7.0 cm, p = 0.013). Surgical site complications were reduced in the CINPT group without statistical difference (30.0% vs. 50.9%, p = 0.064). Fluid drainage and time to drain removal were similar in both groups. The average in-hospital stay was significantly shortened in the CINPT group (10.0 days vs. 13.0 days, p = 0.030). The survey excluded pain, skin irritations, and discomfort during sleep and movement in the CINPT group and showed that the patients felt well protected. This study fails to provide compelling evidence for CINPT to enhance incision healing on the donor site in TMG flap breast reconstruction. There was a trend toward reduced surgical site complications on the donor thigh and the in-hospital stay was shortened. Prophylactic CINPT increases patient comfort and provides a feeling of additional wound protection.
Gesehen am 29.06.2022
This article belongs to the special issue "Updates in aesthetic and reconstructive surgery"